Liver transplantation for non-resectable colorectal liver metastases: the International Hepato-Pancreato-Biliary Association consensus guidelines. (November 2021) - Bonney, Glenn K; Chew, Claire Alexandra; Lodge, Peter; Hubbard, Joleen; Halazun, Karim J; Trunecka, Pavel; Muiesan, Paolo; Mirza, Darius F; Isaac, John; Laing, Richard W; Iyer, Shridhar Ganpathi; Chee, Cheng Ean; et al.
Summary: Colorectal cancer is a prevalent disease worldwide, with more than 50% of patients developing metastases to the liver. Despite advances in improving resectability, most patients present with non-resectable colorectal liver metastases requiring palliative systemic therapy and locoregional disease control strategies. There is a growing interest in the use of liver transplantation to treat non-resectable colorectal liver metastases in well selected patients, leading to a surge in the number of studies and prospective trials worldwide, thereby fuelling the emerging field of transplant oncology. The interdisciplinary nature of this field requires domain-specific evidence and expertise to be drawn from multiple clinical specialities and the basic sciences. Importantly, the wider societal implication of liver transplantation for non-resectable colorectal liver metastases, such as the effect on the allocation of resources and national transplant waitlists, should be considered. To address the urgent need for a consensus approach, the International Hepato-Pancreato-Biliary Association commissioned the Liver Transplantation for Colorectal liver Metastases 2021 working group, consisting of international leaders in the areas of hepatobiliary surgery, colorectal oncology, liver transplantation, hepatology, and bioethics. The aim of this study was to standardise nomenclature and define management principles in five key domains: patient selection, evaluation of biological behaviour, graft selection, recipient considerations, and outcomes. An extensive literature review was done within the five domains identified. Between November, 2020, and January, 2021, a three-step modified Delphi consensus process was undertaken by the workgroup, who were further subgrouped into the Scientific Committee, Expert Panel, and Transplant Centre Representatives. A final consensus of 44 statements, standardised nomenclature, and a practical management algorithm is presented. Specific criteria for clinico-patho-radiological assessments with molecular profiling is crucial in this setting. After this, the careful evaluation of biological behaviour with bridging therapy to transplantation with an appropriate assessment of the response is required. The sequencing of treatment in synchronous metastatic disease requires special consideration and is highlighted here. Some ethical dilemmas within organ allocation for malignant indications are discussed and the role for extended criteria grafts, living donor transplantation, and machine perfusion technologies for non-resectable colorectal liver metastases are reviewed. Appropriate immunosuppressive regimens and strategies for the follow-up and treatment of recurrent disease are proposed. This consensus guideline provides a framework by which liver transplantation for non-resectable colorectal liver metastases might be safely instituted and is a meaningful step towards future evidenced-based practice for better patient selection and organ allocation to improve the survival for patients with this disease.